In-vitro Effects of Tribulusterrestris Extracts on S. aureus - Abdulameer Bedn, Asmaa; Tariq Hammoodi, Omar; Salah Hasan, Mustafa; Naji Saleh, Eman; D Salih, Noman (International Journal of Psychosocial Rehabilitation, 2020)
The current study aimed to assess alcoholic extracts of Tribulusterrestris antibacterial activity on pathogenic S. aureus isolate. An isolate of S. aureus were from a previous study. The ethanolic extract of plant were prepared according to previous studies. This extract was assessed for antibacterial activity by using the diffusion method. The value of inhibition zone diameter for alcoholic extract against S. aureus were 12, 14, 17mm at a concentrations 0.75, 1.5, 3 mg/ml respectively. In conclusion, the 3 mg/ml concentration of extract was more efficient and have an effective antibacterial effect.